2011
DOI: 10.1016/j.jfca.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Development of a rapid assessment method for the prediction of the glycemic index

Abstract: The glycemic index (GI) is a measurement used to classify foods according to their potential for raising blood glucose levels. The GI of a foodstuff is generally measured by determining the increment in blood glucose concentration after the consumption of a test meal over a set period of time and comparing it with an isoglucosidic control meal (normally white bread or glucose) and expressed as a percentage within a group of individuals (in vitro). Rapid analysis methods (in vivo) have been evaluated worldwide,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…However, with regard to cashew (Figure 4), although its GI and GL are low, the initial glycemic peak triggered can be harmful, especially for people who have high fasting glucose level, such as obese patients who have metabolic syndrome and diabetic patients (Brand-Miller et al, 2009a). Gibson et al (2011) also found variations in the glucose level peaks of foods belonging to the same food group. diseases such as diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…However, with regard to cashew (Figure 4), although its GI and GL are low, the initial glycemic peak triggered can be harmful, especially for people who have high fasting glucose level, such as obese patients who have metabolic syndrome and diabetic patients (Brand-Miller et al, 2009a). Gibson et al (2011) also found variations in the glucose level peaks of foods belonging to the same food group. diseases such as diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is resource intensive and relatively time consuming (Gibson et al 2011). Thus, it is resource intensive and relatively time consuming (Gibson et al 2011).…”
mentioning
confidence: 99%
“…The GI is determined in vivo, which requires the use of human subjects for evaluation of the 2 h blood glucose response after food intake. Thus, it is resource intensive and relatively time consuming (Gibson et al 2011). In vitro digestion methods have been developed to determine the sensitivity of starch-enriched food to in vitro enzymatic action (Goñi et al 1997;Germaine et al 2008;Chiou et al 2011), and the results demonstrate a close link between in vitro starch digestion and in vivo GI measurement.…”
mentioning
confidence: 99%
“…Along with the oral sessions on the first and the second day, poster presentations were organised during the session breaks and the two-hour lunch time (Chew et al, 2011;Gibson et al, 2011;Glibetic et al, 2011;Sainsbury et al, 2011;Schö nfeldt et al, 2011).…”
Section: Keynote Addressesmentioning
confidence: 99%